A Need Analysis of Law Students’ English Literacy for Occupational Purposes (EOP) - Noreen, Asima; Madiha Bashir (IJLTP, 2025)
Language is considered as a way of transmitting ideas and feelings from one person to another. There arises a need of a common language which can be best understood in all over the world. English language serves this purpose very well. The major purpose of this study was to investigate the theoretical bases of needs analysis of law graduates’ English literacy for their occupational purposes. A sample of four (02 from district Rawalpindi and 02 from Islamabad) was randomly selected to collect the data. As in some institutions the degree program is of three years and in some of five years that is why the data was collected from the final year students. By using convenient sampling design, a sample of 100 law graduates of final year students of LLB was selected; that is 50 students from district Rawalpindi and 50 from Islamabad. There are more than 1000 lawyers practicing in district Islamabad and Rawalpindi. Out of these, a sample of 100 was selected to collect the data to achieve the objectives of this research study. The finding indicates that most of the students are in need of learn English language in their field as a subject English as Occupational Purpose (EOP). It helps law students in different ways e.g. speaking, reading difficult terms and texts, proceeding, negotiating etc. The major recommendations for future researcher is that to condust a research on need analysis of lawyers from all over the Pakistan.